Garnering Partnerships to Bridge Gaps Among Mental Health, Health Care, and Public Health - Elsie Freeman, MD, MPH; Letitia Presley-Cantrell, PhD, MEd; Valerie J. Edwards, PhD; Sharrice White-Cooper, MPH; Kenneth S. Thompson, MD; Stephanie Sturgis, MPH; Janet B. Croft, PhD (Preventing Chronic Disease, 2010)
Integrating mental health and public health chronic disease programs requires partnerships at all government levels. Four examples illustrate this approach: 1) a federal partnership to implement mental health and mental illness modules in the Behavioral Risk Factor Surveillance System; 2) a state partnership to improve diabetes health outcomes for people with mental illness; 3) a community-level example of a partnership with local aging and disability agencies to modify a home health service to reduce depression and improve quality of life among isolated, chronically ill seniors; and 4) a second community-level example of a partnership to promote depression screening and management and secure coverage in primary care settings. Integration of mental health and chronic disease public health programs is a challenging but essential and achievable task in protecting Americans’ health.